1996
DOI: 10.1128/aem.62.5.1788-1792.1996
|View full text |Cite
|
Sign up to set email alerts
|

Fluorene Oxidation In Vivo by Phanerochaete chrysosporium and In Vitro during Manganese Peroxidase-Dependent Lipid Peroxidation

Abstract: The oxidation of fluorene, a polycyclic hydrocarbon which is not a substrate for fungal lignin peroxidase, was studied in liquid cultures of Phanerochaete chrysosporium and in vitro with P. chrysosporium extracellular enzymes. Intact fungal cultures metabolized fluorene to 9-hydroxyfluorene via 9-fluorenone. Some conversion to more-polar products was also observed. Oxidation of fluorene to 9-fluorenone was also obtained in vitro in a system that contained manganese(II), unsaturated fatty acid, and either crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 43 publications
0
32
0
2
Order By: Relevance
“…Nonetheless, MnP also possesses the capability to oxidize or cleave non-phenolic structures with the contributions of mediators including thiyl or lipid radicals (Abdel- Hamid, Solbiati, & Cann, 2013;Reddy, Sridhar, & Gold, 2003). Moreso, the ability of MnP to oxidize and depolymerize natural and synthetic lignin and as well, recalcitrant compounds has been reported (Bogan, Lamar, & Hammel, 1996;Dehorter & Blondeau, 1993;Hofrichter, 2002;Hofrichter, Steffen, & Hatakka, 2001;Hofrichter, Ullrich, Pecyna, Liers, & Lundell, 2010). MnPs possess two or three residues corresponding to Glu-35, Glu-39 and Asp-175 of Phanerochaete chrysosporium MnP 1 that binds Mn (Floudas et al, 2012;.…”
Section: Class II Heme-peroxidasesmentioning
confidence: 99%
“…Nonetheless, MnP also possesses the capability to oxidize or cleave non-phenolic structures with the contributions of mediators including thiyl or lipid radicals (Abdel- Hamid, Solbiati, & Cann, 2013;Reddy, Sridhar, & Gold, 2003). Moreso, the ability of MnP to oxidize and depolymerize natural and synthetic lignin and as well, recalcitrant compounds has been reported (Bogan, Lamar, & Hammel, 1996;Dehorter & Blondeau, 1993;Hofrichter, 2002;Hofrichter, Steffen, & Hatakka, 2001;Hofrichter, Ullrich, Pecyna, Liers, & Lundell, 2010). MnPs possess two or three residues corresponding to Glu-35, Glu-39 and Asp-175 of Phanerochaete chrysosporium MnP 1 that binds Mn (Floudas et al, 2012;.…”
Section: Class II Heme-peroxidasesmentioning
confidence: 99%
“…The decrease in O 2 concentration in the reactions with oleic acid was less than 0.1 nmol´min 21 . It has been reported that fluorene was decomposed by MnP, Mn(II) and oleate, but the peroxidation started after a lag of 10±20 h [4]. Therefore, the presence of 1,4-pentadienyl moiety is not a prerequisite for MnP-dependent lipid peroxidation but the low dissociation energy of bis-allylic hydrogen (75±80 kCal´mol 21 ) compared with that of allylic hydrogen (88 kCal´mol 21 ) [28] greatly facilitates the induction of peroxidation as is obvious from the reaction rate between linoleic and oleic acid.…”
Section: Oxygen Consumption During Reactions Of Mnp and Mn(iii)-tartrmentioning
confidence: 99%
“…Ovaj početni izvještaj stimulirao je mnoge druge istraživače da pokažu da je lignin degradacioni sistem P. chrysosporium koji uključuje lignin peroksidazu (LiP) i mangan peroksidazu (MnP) značajan u razgradnji PAH--ova [6]. Za izolovane forme LiP i MnP također, bilo je pokazano da su pogodne za oksidaciju antracena, pirena, fluorena i benzo[a]pirena do odgovarajućih hinona [7][8][9]. Lignin, skupa sa celulozom i hemicelulozom, glavna je komponenta drvnog materijala i najobimnija forma aromatičnog ugljenika u biosferi.…”
unclassified